PERAN ASISTENSI MENGAJAR DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI SMP NEGERI 21 KOTA BENGKULU - Mery Jayanti; Fhadila Hannum Lubis; Bayu Arjuna; Siska Putri Anggini; Fitria; Desta Rahmawati; Syamsul Rizal; Tresya Amanda (LPPI UMN AL WASHLIYAH, 2026)
Student learning activeness is one of the key indicators of successful classroom learning. This study aims to describe the role of teaching assistance in improving student learning activeness at SMP Negeri 21 Kota Bengkulu. The teaching assistance program was conducted over eight sessions, involving university students as teaching assistants to support teachers during the learning process. The methods applied included group discussions, presentations, question-and-answer sessions, and reflective activities with teachers. Observations were conducted to assess students’ activeness in asking questions, participating in discussions, collaborating in groups, and presenting their work. The results show that students’ learning activeness increased significantly, interactions between students became more dynamic, confidence and communication skills improved, and the overall quality of learning was enhanced through teacher–teaching assistant collaboration. Reflection sessions also helped teachers and teaching assistants design follow-up activities to optimize future learning sessions. Therefore, teaching assistance is proven to be an effective strategy for increasing student participation, motivation, and communication skills in active learning.